A piezomicrobalance system for high‐temperature mass relaxation characterization of metal oxides: A case study of Pr‐doped ceria. Issue 3 (21st December 2016) - Simons, Philipp; Ji, Ho‐Il; Davenport, Timothy C.; Haile, Sossina M.
Abstract: A system for mass relaxation studies based on a gallium phosphate piezocrystal microbalance has been developed, built, and successfully used to characterize a representative mixed ionic and electronic conducting material. The apparatus is constructed to achieve reactor gas exchange times as short as 2 seconds and temporal resolution in mass measurement of 0.1 seconds. These characteristics enabled evaluation of mass relaxations that occurred on the 6 seconds time scale. Proof of concept for materials characterization capabilities of the system was carried out using 10% praseodymium‐doped cerium oxide (PCO), a material that undergoes, at selected temperatures and oxygen partial pressures, changes in mass but not in conductivity. Thin films were deposited on the piezocrystals via pulsed laser deposition (PLD). Mass relaxation curves were collected at 700°C upon application of a small step change in oxygen partial pressure, p O 2 . Using two different films, the surface reaction constant, k S, was obtained over the p O 2 range from 10 −4 to 0.1 atm. Its value is found to vary between 9.7 × 10 −6 and 1.7 × 10 −4 cm/s, displaying a power law dependence on p O 2, with a law exponent of 0.67 ± 0.02, as averaged over the two sets of results. This steep dependence of k S on p O 2 is surprisingly independent of a change in dominant defect type within the p O 2 range of measurement.